Capital Budgeting Analysis to Assess the Karaoke Business Feasibility - Panji Galih Kusumo Adie (Universitas Negeri Makassar, 2019)
One form of entertainment that is currently being developed and in demand by the people of Jakarta and its surroundings is karaoke. This study aims to determine the results of the investment assessment of Karaoke Taxi using Capital Budgeting techniques in knowing the level of investment feasibility. The results of calculations with the Net Present Value method value of Rp. 92,061,946,333 with an initial capital of Rp. 80,000,000,000. While based on the feasibility analysis using the Profitability Index, the Karaoke Taxi business project got a value of 2.15, this result exceeds the number 1. Based on the feasibility analysis using the Internal Rate of Return a value of 40.18 percent was obtained. For the feasibility analysis using the Discounted Payback Period, the result of the Karaoke Taxi business project will return in the year 3,872, the return of investment is faster than required by the company (4 years).